Mapping shifts in nanopore signal to changes in protein and protein‐DNA conformation. Issue 5 (21st December 2021) - Carlsen, Autumn; Tabard‐Cossa, Vincent
Abstract: Solid‐state nanopores have been used extensively in biomolecular studies involving DNA and proteins. However, the interpretation of signals generated by the translocation of proteins or protein‐DNA complexes remains challenging. Here, we investigate the behavior of monovalent streptavidin and the complex it forms with short biotinylated DNA over a range of nanopore sizes, salts, and voltages. We describe a simple geometric model that is broadly applicable and employ it to explain observed variations in conductance blockage and dwell time with experimental conditions. The general approach developed here underscores the value of nanopore‐based protein analysis and represents progress toward the interpretation of complex translocation signals.